Review of Village Apparatus Knowledge on the Method of Depreciating Village Fix Assets in Several Villages in Bandung and West Bandung Regencies - Silviana,; Anthony, Erwin (International Journal of Psychosocial Rehabilitation, 2020)
Regulations on depreciation of regional property have been issued, but the readiness of regional and village government officials is still questionable. The study was conducted on 24 apparatuses from 8 villages. The results of the review show that the village government apparatus, affected by the depreciation of village property, especially fixed assets, is still very minimal, so it needs to be increased again by attending workshops or training, actively discussing with experts, both government agencies (inspectorate) and universities that have economics faculty, especially accounting departments.